Protests, land rights and riots : postcolonial struggles in Australia in the 1980s - Morris, Barry (Berghahn Books, 2014)
The 1970s saw the Aboriginal people of Australia struggle for recognition of their postcolonial rights. Rural communities, where large Aboriginal populations lived, were provoked as a consequence of social fragmentation, unparalleled unemployment, and other major economic and political changes. The ensuing riots, protests, and law-and-order campaigns in New South Wales captured the tense relations that existed between Indigenous people, the police, and the criminal justice system. In Protests, Land Rights, and Riots, Barry Morris shows how neoliberal policies in Australia targeted those who were least integrated socially and culturally, and who enjoyed fewer legitimate economic opportunities. Amidst intense political debate, struggle, and conflict, new forces were unleashed as a post-settler colonial state grappled with its past. Morris provides a social analysis of the ensuing effects of neoliberal policy and the way Indigenous rights were subsequently undermined by this emerging new political orthodoxy in the 1990s.